The Pharmacist's Role in the Implementation of FASTHUG-MAIDENS, a Mnemonic to Facilitate the Pharmacotherapy Assessment of Critically Ill Patients: A Cross-Sectional Study. - Chaverri Fernández, José Miguel (2022)
FASTHUG is a mnemonic used by intensive care physicians to ensure the proper management of patients admitted to an Intensive Care Unit (ICU). FASTHUG-MAIDENS is a modified version that incorporates key pharmacotherapeutic elements such as delirium management, drug dosing, and drug interactions for an appropriate medication assessment of critically ill patients. An analytical cross-sectional study of hospitalized patients was carried out to determine aspects related to the pharmacotherapeutic management of critically ill patients that required to be optimized, to design and implement a protocol based on the FASTHUG-MAIDENS mnemonic. A total of 435 evaluations were performed to assess the status of current critical patient management. The main parameters with opportunities to be improved were analgesia, feeding, and sedation. With the implementation of MAIDENS, the parameters of analgesia, sedation, and thromboprophylaxis showed an increase in the percentage of optimal management. Furthermore, 103 drug-related problems were detected, and most of them were associated with feeding (21.3%), glucose control (11.7%), and delirium (9.7%). The FASTHUG MAIDENS protocol implementation allows for the evaluation of more vital aspects in the management of critically ill patients. The daily review of patients admitted to the ICU by a clinical pharmacist (CP) using the FASTHUG-MAIDENS checklist instead of the FASTHUG mnemonic facilitates the identification of DRPs for the performance of possible interventions by the CP to improve the pharmacotherapeutic management.